2001
DOI: 10.1074/jbc.m100271200
|View full text |Cite
|
Sign up to set email alerts
|

Aphidicolin Triggers a Block to Replication Origin Firing inXenopus Egg Extracts

Abstract: DNA replication origins are located at random with respect to DNA sequence in Xenopus early embryos and on DNA replicated in Xenopus egg extracts. We have recently shown that origins fire throughout the S phase in Xenopus egg extracts. To study the temporal regulation of origin firing, we have analyzed origin activation in sperm nuclei treated with the DNA polymerase inhibitor aphidicolin. Sperm chromatin was incubated in Xenopus egg extracts in the presence of aphidicolin and transferred to a fresh extract, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 51 publications
(47 reference statements)
4
77
2
Order By: Relevance
“…Aphidicolin is an inhibitor of DNA polymerase alpha that blocks both the elongation and initiation phases of DNA replication in Xenopus egg extracts [18]. We observed that addition of aphidicolin to extracts caused a three-fold increase in the number of CENP-A foci at 60 or 90 minutes, relative to untreated sperm nuclei ( Figure 3A, B and H).…”
Section: Detection Of Cenp-a Foci In the Presence Of F Dna Replicatiomentioning
confidence: 73%
“…Aphidicolin is an inhibitor of DNA polymerase alpha that blocks both the elongation and initiation phases of DNA replication in Xenopus egg extracts [18]. We observed that addition of aphidicolin to extracts caused a three-fold increase in the number of CENP-A foci at 60 or 90 minutes, relative to untreated sperm nuclei ( Figure 3A, B and H).…”
Section: Detection Of Cenp-a Foci In the Presence Of F Dna Replicatiomentioning
confidence: 73%
“…The presence of double-stranded DNA breaks in egg extracts inhibits chromosomal DNA replication as well as entry into mitosis (17)(18)(19). Interestingly, aphidicolin, which inhibits DNA polymerase activity, also triggers a pathway that blocks utilization of as yet unfired origins (24,44). This response is sensitive to the checkpoint-overriding compound caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, an asynchronous population of cells is pulsed-labeled for a short period of time with halogenated nucleotides to determine the position of replication origins (arrowheads). DNA fibers can be counterstained with anti-ssDNA antibodies (blue) (Versini et al 2003), and specific regions can be analyzed by FISH (Lebofsky et al 2006); c DNA combing analysis of densely spaced origins in Xenopus egg extracts (Marheineke and Hyrien 2001). Initiation sites are labeled with DIG-dUTP (red) to mark replication origins (arrowheads) after release from an aphidicolin block and biotin-dUTP (green) is added at variable times until completion of DNA replication; d DNA combing analysis of interorigin distances (IODs) in yeast.…”
Section: Single-molecule Analysis Of Dna Replication Profilesmentioning
confidence: 99%